Comparison of Extended-Spectrum Beta-Lactamase-Producing Escherichia coli Isolates From Rooks (Corvus frugilegus) and Contemporary Human-Derived Strains: A One Health Perspective - Nagy, Bálint József; Balázs, Bence; Benmazouz, Isma; Gyüre, Péter; Kövér, László; Kaszab, Eszter; Bali, Krisztina; Lovas-Kiss, Ádám; Damjanova, Ivelina; Majoros, László; Tóth, Ákos; Bányai, Krisztián; et al. (Frontiers in Microbiology, 2022)
During winter, a large number of rooks gather and defecate at the park of a university clinic. We investigated the prevalence of extended-spectrum beta-lactamase (ESBL)–producing Escherichia coli in these birds and compared recovered isolates with contemporary human isolates. In 2016, fecal samples were collected from 112 trap-captured rooks and investigated for presence of ESBL producers using eosin methylene blue agar supplemented by 2 mg/L cefotaxime; 2,455 contemporary human fecal samples of patients of the clinics sent for routine culturing were tested similarly. In addition, 42 ESBL-producing E. coli isolates collected during the same period from inpatients were also studied. ESBL genes were sought for by PCR and were characterized by sequencing; E. coli ST131 clones were identified. Epidemiological relatedness was determined by pulsed-field gel electrophoresis and confirmed using whole genome sequencing in selected cases. Thirty-seven (33%) of sampled rooks and 42 (1.7%) of human stools yielded ESBL-producing E coli. Dominant genes were blaCTX–M–55 and blaCTX–M–27 in corvid, blaCTX–M–15 and blaCTX–M–27 in human isolates. ST162 was common among rooks. Two rook-derived E. coli belonged to ST131 C1-M27, which was also predominant (10/42) among human fecal and (15/42) human clinical isolates. Another potential link between rooks and humans was a single ST744 rook isolate grouped with one human fecal and three clinical isolates. Despite possible contact, genotypes shared between rooks and humans were rare. Thus, rooks are important as long-distance vectors and reservoirs of ESBL-producing E. coli rather than direct sources of infections to humans in our setting.